Hydraulic conductivity changes in river valley sediments caused by river bank filtration – an analysis of specific well capacity - Kaczmarek, Piotr M.J. (Geologos, 2017)
Parameters from archive data of the Kalisz-Lis waterworks, located in the Prosna River valley south of Kalisz, have been analysed. Well barrier discharges groundwater from Quaternary sediments which is mixed with riverbank filtration water. The analysis focused on specific well capacity, a parameter that represents the technical and natural aspects of well life. To exclude any aging factor, an examination of specific well capacity acquired only in the first pumping tests of a new well was performed. The results show that wells drilled between 1961 and 2004 have similar values of specific well capacity and prove that > 40 years discharge has had little influence on hydrodynamic conditions of the aquifer, i.e., clogging has either not occurred or is of low intensity. This implies that, in the total water balance of the Kalisz- Lis well barrier, riverbank filtration water made little contribution. In comparison, a similar analysis of archive data on the Mosina-Krajkowo wells of two generations of well barriers located in the Warta flood plains was performed; this has revealed a different trend. There was a significant drop in specific well capacity from the first pumping test of substitute wells. Thus, long-term groundwater discharge in the Warta valley has had a great impact on the reduction of the hydraulic conductivity of sediments and has worsened hydrodynamic conditions due to clogging of river bed and aquifer, which implies a large contribution of riverbank filtration water in the total water well balance. For both well fields conclusions were corroborated by mathematical modeling; in Kalisz-Lis 16.2% of water comes from riverbank filtration, whereas the percentage for Mosina-Krajkowo is 78.9%.